Arthroscopic Intra-articular Biceps Tenodesis With All-Suture Anchor - Kevin C. Wang MD; Jeffrey J. Theismann MD; Elliot Cole MD; Alan L. Zhang MD (Video Journal of Sports Medicine)
Background: Biceps tenodesis can be used to treat both superior labral anterior and posterior (SLAP) tears and degenerative biceps pathologies in the setting of rotator cuff pathology or as stand-alone techniques. Research has shown that arthroscopic biceps tenodesis has comparable outcomes to open tenodesis with the benefit of being less invasive. Indications: Surgical indications for intra-articular tenodesis of the long head of the biceps (LHB) include SLAP tear, failed SLAP repair, partial-thickness LHB tear, biceps instability, tenosynovitis, and clinical examination consistent with LHB pain. Technique Description: We present our technique for arthroscopic intra-articular biceps tenodesis with a top-of-the-groove all-suture anchor using percutaneous suture passage with a spinal needle and polydioxanone suture. Sutures are shuttled through the LHB in situ before releasing the tendon from the labrum. Results: The authors have seen excellent clinical results using this method without any cases of tenodesis failure. Prior studies have shown subpectoral, suprapectoral, and top-of-the-groove biceps tenodesis to have similar good clinical outcomes at multiple time points. Discussion/Conclusion: This technique is advantageous as it is time efficient and cost-effective, and tension on the biceps can be easily maintained as suture is passed through the tendon in situ before the tendon is released from the superior labrum. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.